2016
DOI: 10.17140/npoj-2-111
|View full text |Cite
|
Sign up to set email alerts
|

Low Potassium Content Vegetables Research For Chronic Kidney Disease Patients in Japan

Abstract: Chronic Kidney Disease (CKD) is a common disorder to the elderly people, and its prevalence is increasing globally. We are turning into a super-aged society very rapidly and the number of CKD patients with dialysis treatment is now over 310,000 in Japan, which is the second largest population in the world. Japanese researchers have a pioneering status in addressing this issue through basic and clinical nephrology research. In addition, advanced research related to the dietary supplementation of CKD patients is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Using this method, low-K edible parts have been achieved in leafy greens such as spinach, leaf lettuce, Chinese lettuce, komatsuna, and mesclun [ 60 , 61 ], as well as in fruit vegetables including tomatoes, melons, and strawberries [ 59 , 60 , 61 , 62 , 63 ]. It has also been reported that consumption of low-K-containing melons suppresses the increase in serum K concentration in dialysis patients before and after eating [ 64 ]. However, low-K vegetables cannot be cultivated in ordinary outdoor soil because it is necessary to exclude the effect of K contained in soil, which requires a plant factory that can control the cultivation environment, such as hydroponics.…”
Section: Vegetables With Low K Contentmentioning
confidence: 99%
“…Using this method, low-K edible parts have been achieved in leafy greens such as spinach, leaf lettuce, Chinese lettuce, komatsuna, and mesclun [ 60 , 61 ], as well as in fruit vegetables including tomatoes, melons, and strawberries [ 59 , 60 , 61 , 62 , 63 ]. It has also been reported that consumption of low-K-containing melons suppresses the increase in serum K concentration in dialysis patients before and after eating [ 64 ]. However, low-K vegetables cannot be cultivated in ordinary outdoor soil because it is necessary to exclude the effect of K contained in soil, which requires a plant factory that can control the cultivation environment, such as hydroponics.…”
Section: Vegetables With Low K Contentmentioning
confidence: 99%
“… Results from a questionnaire regarding low-potassium melon in 76 dialysis patients (Adopted from Talukder et al, 2016 ). …”
Section: Resultsmentioning
confidence: 99%
“…The main purpose of the second experiment was to provide subjects with impaired kidney function an alternative food product (K-reduced microgreens) to limit K intake. Similarly to the first experiment, the agronomic trial was conducted in a commercial greenhouse to verify how the extensively documented experimental protocols from other studies 7,8,[33][34][35] can be readily applied in a commercial greenhouse context.…”
Section: Methodsmentioning
confidence: 99%